Pemodelan Basis Data Graf untuk Data Obat-Obatan di Indonesia dalam Praktik Swamedikasi - Fadhliana, Nisa Rizqiya; Suryawan, Sayekti Harits; Pratama Mugi , Boby; Amelia, Rizky (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2025)
Self-medication is a practice that is often practiced by the public, especially to overcome common health problems. Self-medication can be done but it must be based on a good understanding and knowledge of the use of drugs and the risks that can be caused, especially when taking drugs that are combined with drugs that have different ingredients. Public awareness of self-medication is still low, this is due to the lack of information obtained about the indications and risks of using over-the-counter medicines. A Graph database is a model that can be implemented well to provide information because it can be visualized in graph form. The implementation of graphs for visualizing medicines to provide knowledge for the community when practicing self-medication is the right solution because it can present data and be well integrated. The system development carried out in providing drug information using graph modeling has provided satisfactory results by providing accurate and relevant responses.   Keywords : Self-medication; Medication; Graph Database; Basis Data Graf; Drugs; Information